2019
DOI: 10.26873/svr-820-2019
|View full text |Cite
|
Sign up to set email alerts
|

FIELD APPLICATION FOR EXPERIMENTAL INACTIVATED MULTI-VALENT P. multocida AND AVIAN INFLUENZA (H9N2) VACCINE IN POULTRY

Abstract: Fowl cholera (FC) and Avian Influenza (AI) are two of the major economically important respiratory and septicaemic disease of poultry in Egypt and allover the world. A field trails was conducted to evaluate the immunogenicity of an experimentally multivalent inactivated Fowl cholera (P. multocida) and Avian Influenza (H9N2) vaccine. The In this study a combined inactivated Montanide ISA fowl cholera and AI vaccine was prepared then the immunization potency and protective efficacy were evaluated through experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The two vaccines in Groups 1-3 had protection rates of 80-100%. These results agree with those of Salama et al [19] who found protection levels of 80-93.3% against Pasteurella multocida and 96.6% against AI virus after challenging with the used virulent strains after the single and booster doses, respectively. Moreover, Ghanem et al [20] found a high degree of protection for layers and chicks with a vaccine prepared from trivalent E. coli (serotypes O1, O2, and O78) and an inactivated Newcastle disease.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The two vaccines in Groups 1-3 had protection rates of 80-100%. These results agree with those of Salama et al [19] who found protection levels of 80-93.3% against Pasteurella multocida and 96.6% against AI virus after challenging with the used virulent strains after the single and booster doses, respectively. Moreover, Ghanem et al [20] found a high degree of protection for layers and chicks with a vaccine prepared from trivalent E. coli (serotypes O1, O2, and O78) and an inactivated Newcastle disease.…”
Section: Discussionsupporting
confidence: 93%
“…In an investigation of HI and ELISA tests of the sera of chickens vaccinated with combined AI (H9N2) and fowl cholera (FC), the study by Salama et al . [ 19 ] indicated similar results until week 6 post-vaccination for FC using Montanide ISA206. In addition, Ghanem et al .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Berdasarkan hasil analisis titer antibodi pascavaksinasi menunjukkan terjadi peningkatan titer antibodi setiap minggu pada kelompok P1 dan P2 dengan rerata titer antibodi kelompok P2 lebih tinggi dibandingkan titer antibodi kelompok kontrol dan P1. Temuan ini sesuai dengan laporan Salama et al (2019) yang menyatakan bahwa inokulasi dosis booster vaksin H9N2 menyebabkan peningkatan titer antibodi yang cepat, dengan puncak titer antibodi AI ditemukan pada minggu ke-3 pasca boostering. Pada vaksinasi ulangan, titer antibodi yang dihasilkan relatif lebih tinggi dan pembentukannya juga lebih cepat dibandingkan dengan vaksinasi pertama.…”
Section: Hasil Dan Pembahasanunclassified